Critical thinking pedagogical practices in medical education: a systematic review - Araújo, Beatriz; Gomes, Sandra F.; Ribeiro, Laura (Frontiers in Medicine, 2024)
The development of critical thinking (CT) has been a universal goal in higher education. A systematic review of the literature was conducted to evaluate the effectiveness of currently used pedagogical practices to foster CT/ clinical reasoning (CR)/ clinical judgment (CJ) skills and/or dispositions in undergraduate medical students. PubMed, Web of Science and Scopus databases were searched from January 2010 to April 2021 with a predefined Boolean expression. Of the 3221 articles originally identified, 33 articles were included by using PICOS methodology. From these, 21 (64%) reported CR pedagogical practices and 12 (36%) CT pedagogical practices. Overall, pedagogical practices such as cognitive/visual representation, simulation, literature exposure, test-enhancing and team-based learning, clinical case discussion, error-based learning, game-based learning seem to enhance CT/CR skills and/or dispositions. Further research is required to identify the optimal timing, duration and modality of pedagogical interventions for effectively foster CT/CR in medical education.